The downward continuation of aeromagnetic data from magnetic source ensembles. Issue 2 (26th March 2019) - Cooper, G.R.J.
ABSTRACT: Downward continuation is a commonly used geophysical filter that is applied to aeromagnetic data. It takes the data and produces from it the data which would have been measured had the sensor been closer to the source. A new downward continuation algorithm is introduced in this study, which is much more stable than the traditional method. It downward continues the data by a distance that is a fraction of the current depth, rather than by a fixed distance. Because of this, the data cannot be continued past the depth of the potential field sources (unlike the conventional method), and so the method is more stable. The method produces different anomaly amplitudes than the conventional method, but this is not an issue if certain further processing techniques (such as sunshading or the tilt angle) are to be used. The method is demonstrated on aeromagnetic data from Southern Africa.